Dorothea Eliza Smith, artist of "The Fruits of the Lima market". Issue 2 (October 2014) - Vega, Fernando E.; Fisher, Kimberley; Willis, Tony
<x xml:space="preserve">Abstract</x> An unpublished collection of watercolours entitled "The Fruits of the Lima market. by Mrs. D. E. Smith, between the years 1850 & "53" can be credited to Dorothea Eliza Smith (1804–1864), wife of the Scottish physician Archibald Smith (1797–1868) who published Peru as it is. The watercolours were once in the Crewe Hall library and were purchased by Paul and Rachel Mellon in 1957. They are now in the Oak Spring Garden Library in Virginia, USA. The identification of the artist has also revealed fascinating aspects in the life of the Smith family, including a tragedy at sea off the coast of Peru and a personal art collection that included works by van Dyck, Murillo, Jordaens, Andrea del Sarto, and Zurbarán, among others.